Odpowiedzi

Najlepsza Odpowiedź!
2010-02-22T18:52:31+01:00
A)
x = -2

(x²-3x-5)+(2x²+4x+6)-(-x²-x+2)= (-2² -3 * (-2) - 5) + (2* (-2)² + 4 * (-2) + 6) -
(-(-2)² - (-2) + 2) = (4 + 6 - 5) + (2 * 4 + (-8) + 6) - (-4 -2 + 2) = 5 + 6 + 4 = 15

b)
x =1
y = -5

-(5y+3x²)-(7x-4y)+12 = - (5 * (-5) + 3 * 1²) - ( 7 * 1 - 4 * (-5) ) + 12 = (-25 + 3) - (7 + 20) + 12 = -22 - 27 + 12 = 5 + 12 = 17
2010-02-22T19:02:06+01:00
1) [(-2)²-3*(-2)-5]+[2*(-2)²+4*(-2)+6]-[-(-2)²-(-2)+4]=
=(4+6-5)+(8-8+6)-(-4+2+2)=5+6=11

2) -[5*(-5)+3*1²]-[7*1-4*(-5)]+12=
=-(-25+3)-(7+20)+12=22-27+12=7